Analysis Of Audit Fee Determinants In Manufacturing Companies In Indonesia Stock Exchange - Lasniroha, Magdalena; Purwohedi, Unggul; Handarini, Dwi (LPPM Universitas Negeri Jakarta, 2022)
This study's objective is to investigate and offer empirical evidence concerning the impact of the Independent Board of Commissioners, Company Profitability, Company Complexity, Company Risk, and Internal Audit Function on Audit Fee. In this study, the population comprised of 153 Manufacturing Companies listed between 2017 and 2019 on the Indonesia Stock Exchange (IDX). In addition, the number of observations in this study comprised of 78 observations from 26 manufacturing companies listed on the IDX between 2017 and 2019, which were selected based on the sample selection criteria and the outcomes of theclassical assumption test. Multiple regression equations were used to examine the study's data. Audit fees were not significantly affected by independent commissioners, company risk, or the internal audit function. It is evident from these data that the auditor's determination of the magnitude of the audit fee is influenced by the firm's level of profitability and complexity; consequently, the company must consider its complexity and financial performance to ensure that the audit fees it pays are suitable